Research on Adolescent Reproductive Health in Six High Schools in Kailali (2016)
Background: Kailali, in the Far Western Development Region, is one of the poorest and underdeveloped areas in Nepal. The area is mainly rural, with the majority of people relying on subsistence farming. Like other areas of Nepal, the adolescent population makes up a large percentage of the area (making up more than 1/5 of the total population). Due to the high illiteracy rates, early marriage and childbearing ages, cultural conservativeness and neglected undevelopment and poverty exist in the Far West. The overall purpose of this study is to provide baseline information about the level knowledge, attitude and practice (KAP) among adolescent students on the topics and issues related to Reproductive Health and Adolescent Reproductive Health. Methods: The 6 High Schools were selected to give the greatest cross-section of students in the District of Kailali. Thus 3 urban and 3 rural schools were chosen and different levels of schools (poor government, moderate government, private) were selected. The data was collected by responses from a questionnaire developed and written by the CICD research team. This questionnaire was designed to cover all components of RH and ARH. The research team themselves did the research data analysis. Quantitative data was translated and compared in both English and Nepali to ascertain the best understanding of the answer. The answers were counted and recorded by school, categories were developed by subject/answer and numbers were selected by category. Quantitative answers were also broken down by school, answers counted and recorded in tables designed by Center for Integrated Community Development, and percentages were also recorded. Percentages were calculated by the total number of students in most cases, in others by number of respondents. In all types of data, answers were recorded and tabulated to easily discover if there was any discrepancy between rural/urban/private/government schools. Results: Adolescents in this area do not seem to be as acquainted with sex education on one hand, nor do they seem to possess adequate knowledge about reproductive health; even their awareness toward high priority campaigns with extensive media exposure such as HIV/AIDS is far lower than expected. For example, a majority of students could not differentiate between HIV positive and HIV negative. With regard to their attitude toward sex, it was found that often they took it as a means of physical pleasure no matter how catastrophic the results might be after unsafe practices. This can be illustrated by the 25% of students who reasoned that they had to make an agreement for sex for it to bring pleasure. Conclusions: The adolescents lack necessary access to information about safe sex, family planning, standards of reproductive health as essential to their knowledge for building careers (and staying in school), safe mothering, and appropriate attitudes toward sex. Keywords: adolescents; high schools; reproductive health; rural; urban.